MOTIF MENONTON CHANNEL YOUTUBE ATTA HALILINTAR PADA ANGGOTA A-TEAM - Yeni Anggreni; Genny Gustina Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The research begins with the author's interest in the number of viewers of Atta Halilintar video which has the highest number of subcriber in Southeast Asia on the YouTube platform that is able to compete with other YouTubers only in YouTube or in the form of videos. Ateam is Atta Halilintar's fanbase who idolizes Atta as a YouTuber. Atb Halilintar or Ateam Fanbase members as subjects in the study have their own reasons for wanting to watch the Atta Halilintar YouTube channel. Researchers can convert to un missatge causat per motius and per motivar el canal by watching YouTube Atta Halilintar on Ateam Members.          This research uses the theory of phenomenology of Alfred Schutz which is because of motive and in order to motive from the actions of atheam members who want to watch YouTube channel Atta Halilintar. By using qualitative methods with a phenomenological tradition. Data collection techniques carried out by means of participant observation and in-depth interviews. This study uses subject-based taking techniques based on the objectives. Data analysis in this research is a descriptive analysis technique.          The results of the study revealed that because of motive A-team members wanting to watch Atta Halilintar's YouTube channel was due to the personality and creative factors of Atta Halilintar. Whereas the objectives to be achieved or in order to motive A-team members to watch YouTube channel Atta Halilintar are related to motivation and entertainment. The four motives above that answer the question what are the motives for watching YouTube channel Atta Halilintar to A-team members.